Vacuum-Assisted Closure and Muscle Flap as An Alternative Modality for Infected Wound After Orif of Tibial Fracture: Case Report - OK Ilham Abdullah Irsyam; Saraswati Hastika; Hendra Hendra; Andrew Budiartha Budisantoso; Tesar Akbar Nugraha (Universitas Airlangga, 2022)
Background: The blood supply of a bone can be decreased due to the use of an implant, leading to wound-bed bacterial colonization and the development of the SSI. The principle of vacuum-assisted closure (VAC) is to use a negative pressure environment in the wound to promote increased wound healing. The case shows that VAC application and muscle flap therapy provide the definitive healing of infected wounds after ORIF. Case Report: A 45 years-old male presented with a close comminuted proximal third right tibia fracture and tense skin. The fracture was openly reduced and internally fixated with plate fixation and a skin flap on the fracture area. Still, the wound could not be closed due to difficulty covering the wound, so a counter incision was made. After four days, the patient developed necrosis in the post-operation wound and subsequently underwent debridement and muscle flap with VAC application. Discussion: SSI can be treated by applicating of appropriate antibiotic and surgical procedures. In this case, the infection was treated using third-generation cephalosporin antibiotic, debridement, dissection, and re-elevation of gastrocnemius muscle flap covering the exposed plate area in inferior, split skin graft above the muscle flap and VAC above skin graft with 75 mmHg pressure. Conclusion: Debridement with muscle flap and application of VAC in the deep infected wound of open reduction and internal fixation was found to be successful methods in minimizing complications and obtaining an optimal outcome. This finding was associated with accompanying morbidities or a good wound healing process.